2005
DOI: 10.22358/jafs/67031/2005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exogenous leptin on pancreatic enzyme secretion in anaesthetized rats

Abstract: The influence of leptin on the secretion of pancreatic juice was examined in biliary-pancreatic duct-cannulated anaesthetised rats. Exogenous leptin was given in boluses either intravenously or intraduodenally. A low dose of leptin (0.1 μg/kg BW) had no effect on pancreatic secretion. Leptin in a dose of 1 μg/kg BW given intravenously inhibited protein and amylase output only when the exocrine pancreas was stimulated by CCK-8 (12 pmol/kg BW, iv). Leptin in a high, pharmacological dose (10 μg/kg BW) given intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…In a study reported by Matyjek et al (23), a significant reduction in the volume of secreted pancreatic juice was observed in fundectomized rats, compared to control animals. In addition, there was a decrease in the total protein content without changes in the level of trypsin in the pancreatic juice in fundectomized rats (23). In the present study, the pancreatic homogenates of ANT and Gx rats exhibited an increase in amylase activity by 30% and 47%, respectively.…”
Section: Resultssupporting
confidence: 49%
“…In a study reported by Matyjek et al (23), a significant reduction in the volume of secreted pancreatic juice was observed in fundectomized rats, compared to control animals. In addition, there was a decrease in the total protein content without changes in the level of trypsin in the pancreatic juice in fundectomized rats (23). In the present study, the pancreatic homogenates of ANT and Gx rats exhibited an increase in amylase activity by 30% and 47%, respectively.…”
Section: Resultssupporting
confidence: 49%
“…After thawing, 1 g of mucosa was homogenized with 5 ml of distilled water and centrifuged for 5 min at 1.000 × g at 4°C. The total protein content of supernatant was determined in accordance with the Lowry method modified to be performed in 96-microwell (Matyjek et al, 2004). Maltase and sucrase activities were determined (Dahlqvist, 1984) with minor modifications.…”
Section: Effect Of Feeding Transcarpathian Zeolite On Gastrointestinamentioning
confidence: 99%
“…In cases of low-caloric diets and chronic exercise, ghrelin levels were increased; and in states of obesity or after glucose challenge, the concentrations of this peptide were reduced (Meier and Gressner, 2004;. Ghrelin stimulates the release of the growth hormone from the pituitary gland and increases appetite, food intake, body weight (BW), energy balance and especially fat tissue by decreasing fat oxidation in the liver (Matyjek et al, 2004;Barazzoni et al, 2005). The value of this peptide decreases over the period of childhood and puberty (Broglio et al, 2003).…”
Section: Introductionmentioning
confidence: 99%